Circulation of immigrants to Hungary - Illés, Sándor (Migration Letters, 2015)
Abstract We measure the demographic patterns associated with international circular migration. Firstly, we define the circulation within the conceptual framework of transnationalism. Secondly, we create macro-scale data bank on long-term international circular migrants based on an original statistical method. Thirdly, we seek to gain further insight into the composition of international circular immigrants by gender, age, and family status. Conclusions indicate the need for future research.